"How did you become political?": Narratives of junior researcher-practitioners in applied linguistics. Issue 4 (2nd October 2018) - Häusler, Angela H.; Leal, Priscila; Parba, Jayson; West, Gordon B.; Crookes, Graham V.
ABSTRACT: This article is based on a set of short narratives from four researchers in applied linguistics, who adopt the descriptor "junior political researcher-practitioners." These individuals shared and analyzed these narratives relating to their personal experiences and an emerging political identity in the academy under investigation in this study. The study was methodologically inspired by collective memory-work, a research framework with transformative aspirations that integrates narrative writing with group analysis and dissolves the boundaries between theory and method as well as researcher and research participants. The study itself enacts an inquiry. The narratives are presented for readers to read and respond to. They constitute the joint object of an inquiry by the coauthors and their readers. Other language educators with goals for personal and sociopolitical development may find themselves in this study and be encouraged into embracing their own political potential.